Personalised penetrance estimation for C9orf72-related amyotrophic lateral sclerosis and frontotemporal dementia - Kevin Talbot; Martin R Turner; Alexander G Thompson; Andrew G L Douglas (BMJ Neurology Open, 2024)
Background C9orf72 hexanucleotide repeat expansions are the most common genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) in European populations. Variable disease penetrance between families presents a challenge for genetic counselling of at-risk relatives and reduces the predictive utility of testing asymptomatic relatives. We have developed a novel model for estimating penetrance in individual families affected by C9orf72 using available family history information, allowing the calculation of personalised risk estimates.Methods Published aggregated age-of-onset data for C9orf72-related ALS/FTD were used to generate age-related cumulative relative risks for at-risk relatives within pedigrees. Age-related relative risks are combined with a priori chance of individuals carrying an expansion based on known pedigree information. Penetrance is calculated as a number of affected individuals divided by the sum of cumulative age-related risks of relatives being affected by 80 years.Results This method allows family-specific penetrance to be estimated from family history and at-risk relatives’ personalised age-related ALS/FTD risks to be calculated and illustrated graphically. Penetrance reduces as the number and age of at-risk unaffected relatives increases.Conclusions Family history remains the best indicator of penetrance in C9orf72 expansion carriers. Calculating family-specific penetrance can aid genetic counselling by allowing at-risk relatives a more accurate understanding of their individual risk.